MENINGKATKAN KEMAMPUAN BERBAHASA ANAK USIA DINI MELALUI BERCERITA: IMPROVING CHILDREN'S LANGUAGE SKILLS EARLY THROUGH STORYTELLING - Putri, Shafira Ramadhani Amanda; Hanifa, Hasti Maulidia; Munawaroh, Hidayatu (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2025)
This research aims to explore and analyze the effectiveness of storytelling methods in improving the language skills of young children. This method was chosen as the main focus because it has the potential to stimulate language development in critical periods of children's growth. The research was conducted through an experimental approach involving two control and intervention groups consisting of children aged 3-5 years from local kindergartens. The intervention group took part in structured storytelling sessions designed to stimulate language comprehension, vocabulary, and speaking skills. Meanwhile, the control group took part in conventional learning activities without a special focus on storytelling methods. Data was collected through observation, written tests, and interviews with teachers and parents. The results showed a significant improvement in the language skills of the intervention group compared to the control group. Children who engage in the storytelling method show marked improvements in language comprehension, verbal expression, and vocabulary mastery. These findings support the hypothesis that the storytelling method can be effective as a learning approach to improve the language skills of young children.